2013
DOI: 10.1038/ijo.2013.206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of brown adipose tissue on body fatness and glucose metabolism in healthy humans

Abstract: BAT, independent of age, sex and body fatness, has a significant impact on glucose metabolism in adult healthy humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
240
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(270 citation statements)
references
References 26 publications
12
240
9
1
Order By: Relevance
“…They demonstrated that BAT activity was also negatively correlated with age, body fatness, and glucose metabolism. However, there were no sex differences in the BAT activity; 6,22 this was inconsistent with results of the aforementioned oncology studies, in which experimental cold exposure was not utilized. Thus, the difference in the sensitivity, between men and women, to mild outdoor cold exposure might be prominent in oncology studies.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…They demonstrated that BAT activity was also negatively correlated with age, body fatness, and glucose metabolism. However, there were no sex differences in the BAT activity; 6,22 this was inconsistent with results of the aforementioned oncology studies, in which experimental cold exposure was not utilized. Thus, the difference in the sensitivity, between men and women, to mild outdoor cold exposure might be prominent in oncology studies.…”
contrasting
confidence: 54%
“…[11][12][13][14][15][16][17]19,20 However, in younger healthy individuals, who were exposed to cold, the ratio was much higher (∼50% to 100%). 3,6 With regards to the effect of AmT on the activation of BAT, the results are conflicting with one study demonstrating that the rise in the BAT activity was delayed by a few months in association with a beginning in the decline in the AmT 11 and the other study stating that BAT activity was higher in early winter than late winter or early spring. 21 Matsushita et al 6 and Yoneshiro et al 22 showed that functional BAT could be epidemiologically evaluated using cold-stimulated 18 FDG-PET∕CT, in relatively healthy younger adults.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…Importantly, the idea that the presence of metabolically active BAT would be beneficial for a healthy metabolic phenotype also in humans is supported by several studies showing that the presence of BAT is associated with a low body mass index, low total adipose tissue content and a lower risk of type 2 diabetes. 8, [11][12][13][14] Interestingly, apart from the association between BAT and a healthy metabolic phenotype, there is also growing evidence suggesting a connection between the presence of BAT and bone anabolism. Recent human studies have shown positive correlations between BAT volume and both bone cross-sectional area and bone density.…”
Section: Introduction and Search Strategymentioning
confidence: 99%
“…Moreover, once BAT is activated by cold there is a down-regulation in the expression of angiopoietin-like 4 (ANGPTL4), a protein that inhibits LPL activity; this leads the activation of AMPK, enhancing plasma LPL activity and uptake of plasma triglyceridederived fatty acids [112]. Matsushita et al [114] showed that subjects with detectable BAT have lower total plasma cholesterol and LDL-C than subjects without detectable BAT and De Lorenzo et al [115], showed that 90 days daily exposure to cold (14°C) for 20 min reduced total cholesterol, LDL-C, and BMI in hypercholesterolemic individuals. Whether this mechanism is important in humans for the regulation of lipoprotein metabolism and the risk for atherosclerosis has yet to be proven.…”
Section: Activation Of Bat For the Improvement Of Lipid And Glucose Mmentioning
confidence: 99%